Ferrocene–Biotin Conjugates: Synthesis, Structure, Cytotoxic Activity and Interaction with Avidin. Issue 11 (19th August 2016) - Błauż, Andrzej; Rychlik, Błażej; Makal, Anna; Szulc, Katarzyna; Strzelczyk, Paweł; Bujacz, Grzegorz; Zakrzewski, Janusz; Woźniak, Krzysztof; Plażuk, Damian
Abstract: Friedel–Crafts acylation of ferrocene withd ‐biotin, d ‐homobiotin andd ‐desthiobiotin gave ferrocenyl ketones. These compounds were diastereoselectively reduced to the corresponding alcohols using ( R )‐ and ( S )‐Me‐CBS‐oxazaborolidine–borane complexes as reducing agents. The alcohols were further transformed into azido and finally to amino derivatives with retention of configuration, as confirmed by X‐ray crystallography. Ferrocenylbiotin alcohols smoothly underwent dehydration to ( E )‐alkenes as the major isomers by heating in diluted acetic acid. The synthesized compounds retained high affinity for avidin. They also exhibited high cytotoxicity toward cancer cells expressing various levels of sodium‐dependent multivitamin transporter (SMVT) in the absence of biotin in the medium, whereas the presence of free biotin decreased their antiproliferative activity. This revealed that these biotin–ferrocene conjugates might be used as biologically active agents against cancer cells, although there was no clear relationship between their cytotoxicity and cellular SMVT level. Abstract : Of avid‐in‐terest for cancer : Ferrocene conjugates of biotin, homobiotin, and desthiobiotin bearing hydroxy, azido, amino or alkene groups, instead of the carboxylic moiety of biotin were synthesized. The compounds exhibited high cytotoxic activities toward cultured cancer cells expressing various levels of sodium‐dependent multivitamin transporter. The X‐ray structure of α‐ferrocenylbiotinol in complex with avidin confirmed the high affinity of these derivatives for avidin.